KAJIAN IRIGASI MIKRO PADA SISTEM HIDROPONIK PADI (ORIZA SATIVA L.) VARIETAS SERAYU DALAM RUMAH TANAMAN - Moningka, Christian N. G.; Ludong, Daniel P. M.; Rumambi, David P. (Fakultas Pertanian, Universitas Sam Ratulangi, 2020)
ABSTRACTThe purpose of this study was to examine the effect of the thickness of irrigation water flow in the Deep Flow Technique (DFT) hydroponic system on the amount of plant water requirement (or evapotranspiration) and the Water Use Efficiency (WUE) in rice cv. Serayu at the vegetative phase. This research was carried out in a tropical greenhouse roofed with polyethylene (PE) plastic film. The treatments in this study were three kinds of thickness of Â micro irrigation in the DFT hydroponic system, i.e. 2, 4 and 6 cm. The results showed that water requirement for each planting hole in rice plants during the vegetative phase (60 days) were 14.3650, 12.7025, and 11.3108 with biomass of 62.4576, 58.2874 and 52.6370 g, respectively for 6, 4 and 2 cm. The water use efficiency in 2, 4, 6-cm-DFT-system were 2.3268, Â 2.293 and 2.1740 g/L, respectively.Â Keywords: Hidroponics, Deep Flow Technique, Evapotranspiration, Water Use Efficiency